Phytochemical Analysis, Antioxidant, and Antibacterial Activity of Bidara laut (Strychnos lucida R.Br) Grown in West Bali National Park, Indonesia: Phytochemical Analysis, Antioxidant, and Antibacterial Activity of Bidara laut - Krisnawati; Anita Apriliani Dwi Rahayu; Lisna Hidayati; Rizki Arisandi; Ganis Lukmandaru (Journal of Tropical Life Science, 2025)
Strychnos lucida R.Br. is a medicinal plant believed to treat various diseases. The study aimed to identify the phytochemical compounds, total phenolic content (TPC), antioxidant, and antibacterial activity of the root, seed, stem, and leaf of S. lucida. Antioxidant activity was examined using the DPPH method in the methanol extract. The extract of four parts of S. lucida was tested against three bacteria (Bacillus subtilis Inacc-B334, Staphylococcus aureus Inacc-B4, and Escherichia coli Inacc-B5) using the disk diffusion method. The results showed that alkaloids and tannins were detected in all parts of the plant. The highest TPC was shown in root (6%) and the lowest TPC was found in seed extract (4.67%). The antioxidant activity test presented the value of IC50 of the methanol extract of root, seed, stem, and leaf as 129.65 µg/ml, 255.04 µg/ml, 145.28 µg/ml, and 112.96 µg/ml, respectively. Furthermore, the stem showed antibacterial activity by inhibiting the growth of B. subtilis and S. aureus in a concentration of 10% of the sample extract (v/v). Leaf extract has activity against only S. aureus growth in different concentrations (2.5, 5, 10%), while all bacteria were resistant to root and seed extracts. The stem extract showed the highest antioxidant and antibacterial activity compared to other parts.